Assessments of Birth Outcome of Twin Delivery and Associated Factors among Newborns in Dessie Referral Hospital, Dessie, Ethiopia, 2019 - Nigusie Abebaw; Mohammed Abdu; Natnael Girma (Hindawi Limited, 2021)
Background. There was a fast improvement of twin's birth outcomes in the past decade, but it was average in developing countries. Stillbirth, preterm birth, low birth weight, and birth asphyxia are the major contributors to poor twin birth outcomes. This study was crucial to address the gaps and clarify the outcome of twin delivery. Objectives. To assess the birth outcome of twin delivery and associated factors among newborns who were delivered in Dessie Referral Hospital, Ethiopia, 2019. Methods. Institutional-based retrospective cross-sectional study was employed among 385 maternal records from Nov 10/2013 to Dec 10/2019. Data were selected by using a random sampling technique. Frequencies, proportion, and summary statics were used to describe the study population. The data were entered into Epi Info and exported in the SPSS version 20 for analysis. All variables with p value<0.20 in bivariable logistic regression analysis were considered for multivariable logistic regression analysis; adjusted odds ratio with 95% confidence interval was used to measure the association variable with p value<0.05 which was statistically significant. Results. This finding showed that the prevalence of twin birth outcome accounts 23.4% (95 % CI, 19.2-27.5). Low birth weight 9.1%, stillbirth 4.2%, Apgar score < 7 9.1%, and neonatal death 1 % were accounted. Hypertension disorder (95% CI, 6.01(2.43-14.87)), rural residence (95% CI 2.46(1.39-4.37)), PROM (95% CI 6.39(2.52-16.16)), and no ANC follow-up (95% CI, 13.47(2.49-72.85)) were significantly associated with adverse twin birth. Conclusions and Recommendations. Magnitude of twins' adverse birth outcome was 23.4%. Hypertension disorder, rural residence, PROM, and no ANC follow-up were significant variables for twins' adverse birth outcome. Therefore, all healthcare providers should give sustainable educations and instructions about the importance of sticking with the recommended ANC follow-up.